Secessionism in African Politics
XXIII, 501 p. 6 illus.
Keywords: Secessionism perseveres as a complex political phenomenon in Africa, yet often a more in-depth analysis is overshadowed by the aspirational simplicity of pursuing a new state. Using historical and contemporary approaches, this edited volume offers the most exhaustive collection of empirical studies of African secessionism to date. The respected expert contributors put salient and lesser known cases into comparative perspective, covering Biafra, Katanga, Eritrea and South Sudan alongside Barotseland, Cabinda, and the Comoros, among others. Suggesting that African secessionism can be understood through the categories of aspiration, grievance, performance, and disenchantment, the book's analytical framework promises to be a building block for future studies of the topic. .